THE FLIPPED CLASSROOM: THE PRACTICE OF LEARNING ENGLISH FROM NURSING STUDENTS - Chairuddin, Chairuddin; Arbaiyah, Arbaiyah; Zulida, Evi (Universitas Islam Sumatera Utara (UISU), 2024)
This research aimed to examine the impact of the flipped classroom model on the activities and learning achievement of nursing students in Aceh, with a focus on speaking skills. The study employed classroom action research and was conducted over three months during the odd semester of 2024/2025, involving one first-grade class consisting of 32 students. The research was carried out in two cycles, utilizing pre-test and post-test evaluations to measure student learning outcomes. Additionally, two observers monitored classroom activities and provided reflections for improvement. The results showed a significant improvement in students' speaking skills. The average pre-test score was 55, which increased to 64 after Cycle I and further to 80 after Cycle II. Observations indicated that students became more active and engaged during the learning process, reflecting the effective implementation of the flipped classroom model. These findings suggest that the flipped classroom design successfully enhanced students' speaking abilities, as evidenced by the consistent improvement in their scores across cycles.